2023
DOI: 10.1108/ijbm-06-2022-0256
|View full text |Cite
|
Sign up to set email alerts
|

Amidst technology, environment and human touch. Understanding elderly customers in the bank retail sector

Abstract: PurposeUsing retail banking as a setting and focusing specifically on elderly customers (i.e. individuals aged 60 or more), this study aims to deepen the current understanding of how the physical context and the need for human interaction influence elderly customers' attitudes toward self-service technologies (SSTs) and their behavior.Design/methodology/approachUsing face-to-face questionnaires, a sample of 505 elderly bank customers was collected. Data were analyzed using a multi-method approach, combining a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 143 publications
(345 reference statements)
0
1
0
Order By: Relevance
“…When social contact is essential, internet banking will be rejected because of the lack of human interaction [36]. Customers with a high need for interaction with service personnel prefer counter services because they tend to think they cannot use SST properly [38,39]. In another study, [20] found that the need for interaction did not significantly moderate SST use behavior.…”
Section: Consumer Traitsmentioning
confidence: 99%
“…When social contact is essential, internet banking will be rejected because of the lack of human interaction [36]. Customers with a high need for interaction with service personnel prefer counter services because they tend to think they cannot use SST properly [38,39]. In another study, [20] found that the need for interaction did not significantly moderate SST use behavior.…”
Section: Consumer Traitsmentioning
confidence: 99%